Brief Report: A High Rate of β7+ Gut-Homing Lymphocytes in HIV-Infected Immunological Nonresponders is Associated With Poor CD4 T-Cell Recovery During Suppressive HAART. (1st July 2016) - Girard, Alexandre; Vergnon-Miszczycha, Delphine; Depincé-Berger, Anne-Emmanuelle; Roblin, Xavier; Lutch, Frederic; Lambert, Claude; Rochereau, Nicolas; Bourlet, Thomas; Genin, Christian; Paul, Stéphane
Abstract : Objective: Correlation between GALT homing markers on lymphocytes and the low blood CD4 T-cell reconstitution in immunological nonresponders (INRs) has been studied. Design: Thirty-one INRs, 19 immunological responders (IRs), and 12 noninfected controls were enrolled in this study. INRs were defined by an undetectable plasma viral load RNA less than 40 copies per milliliter and CD4 + T-cell count <500 cells per cubic milliliter in at least 3 years. Methods: A complete peripheral and mucosal lymphocyte immunophenotyping was performed on these patients with a focus on the CCR9, CCR6, and α4β7 gut-homing markers. Results: A highly significant upregulation of α4β7 on INRs peripheral lymphocytes compared with that of IRs has been observed. This upregulation impacts different lymphocyte subsets namely CD4 +, CD8 +, and B lymphocytes. The frequency of β7 + Th17 and Treg cells are increased compared with IRs and healthy controls. The frequency of β7 + CD8 + T cells in the blood is negatively correlated with integrated proviral DNA in rectal lymphoid cells in contrast to β7 + CD4 + T cells associated with HIV integration. Conclusions: Alteration of lymphocyte homing abilities would have deleterious effects on GALT reconstitution and could participate to HIV reservoir constitution. These results emphasize the great interest to consider α4β7-targeted therapy in INR patients to block homing of lymphocytes and/or to directly impair gp120-α4β7 interactions. Abstract : Supplemental Digital Content is Available in the Text.